Diesel emissions and their control - Majewski, W. Addy; Jääskeläinen, Hannu (Warrendale, PA SAE International, 2023)
This book offers a comprehensive overview of how diesel engines work and how their emissions are measured, regulated, and controlled. It covers key topics like pollutant formation, aftertreatment systems (e.g. DPF, SCR), emission standards, fuel quality, and recent technological advancements in reducing diesel engine emissions.
Includes bibliographical references and index
Keywords: Công nghệ kỹ thuật ô tô